Bank Rakyat: the public perceptions on its financial products and marketing strategies / Reeni Zuraini Abdul Ghani - Abdul Ghani, Reeni Zuraini (2010)
This exploratory research was carried out on Bank Rakyat Rawang Branch with the aim to change the public perception about financial products provided by Bank Rakyat and effectiveness of marketing strategies in Bank Rakyat. This study was based on simple random sampling method based on Bank Rakyat customers and the data was collected after they are answers the entire question required. This study also implemented on 50 respondents from various governments department, individuals and also private sectors. Questionnaires were distributed and the data gathered was analyzed to derive possible findings of the study. It is hoped that the findings of the study will highlight the knowledgeable of public about financial products and the level of marketing strategies provided by Bank Rakyat. This research also included some recommendations that related to the study which is can change public perception about financial products and make marketing strategies more effective. Recommendations and suggestions on how to improve the marketing strategies in Bank Rakyat and perception of publics about financial products have been identified. Furthermore, implications for future research are also being discussed for achieving further contribution in fields banking institutions.